Remainders Are Fun 3

Algebra Level 4

Let f ( x ) f(x) be the remainder when the expression 3 x 2017 x 2015 + 4 x 1998 + x 100 + 5 x 2 + 9 3x^{2017} - x^{2015} + 4x^{1998} + x^{100} + 5x^2 + 9 is divided by x 4 + 1 x^4 + 1 .

Evaluate f ( 1 ) f(1) .


For more problems like this, try answering this set .


The answer is 13.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Christian Daang
Apr 3, 2017

By remainder theorem, x 4 = 1 x^4 = -1

then,

3 x 2017 = 3 ( x 4 ) 504 x 3 ( 1 ) x = 3 x x 2015 = ( x 4 ) 503 x 3 ( 1 ) x 3 = x 3 4 x 1998 = 4 ( x 4 ) 499 x 2 4 ( 1 ) x 2 = 4 x 2 x 100 = ( x 4 ) 25 ( 1 ) = 1 5 x 2 = 5 x 2 5 x 2 = 5 x 2 9 = 9 9 = 9 \begin{aligned} 3x^{2017} & = 3(x^4)^{504} \cdot x & \equiv 3(1)x & = 3x \\ -x^{2015} & = -(x^4)^{503} \cdot x^3 & \equiv -(-1)x^3 & = x^3 \\ 4x^{1998} & = 4(x^4)^{499} \cdot x^2 & \equiv 4(-1)x^2 & = -4x^2 \\ x^{100} & = (x^4)^{25} & \equiv (-1) & = -1 \\ 5x^{2} & = 5x^2 & \equiv 5x^2 & = 5x^2 \\ 9 & = 9 & \equiv 9 & = 9 \end{aligned}

f ( x ) = 3 x + x 3 4 x 2 1 + 5 x 2 + 9 = x 3 + x 2 + 3 x + 8 f ( 1 ) = 1 + 1 + 3 + 8 = 13 \therefore f(x) = 3x + x^3 - 4x^2 - 1 + 5x^2 + 9 = x^3 + x^2 + 3x + 8 \implies \boxed{f(1) = 1 + 1 + 3 + 8 = 13}

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...